2016
DOI: 10.3892/etm.2016.3271
|View full text |Cite
|
Sign up to set email alerts
|

Depression in patients with chronic hepatitis B and cirrhosis is closely associated with the severity of liver cirrhosis

Abstract: Abstract. Depression in patients with chronic hepatitis B (CHB) can affect the quality of life, disease diagnosis and case fatality rate. The aim of this study was to explore depression in patients with CHB and cirrhosis, and the effect of the severity of liver cirrhosis on the depressive emotional state. The depressive emotional state was investigated using the Hamilton Depression Scale (HAMD) and Hamilton Anxiety Scale (HAMA) in 114 patients with CHB and cirrhosis, comprising 42 cases classified as Child-Pug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 9 publications
3
24
1
1
Order By: Relevance
“…Interestingly, patients receiving treatment for CHB did not convey an increased risk for bipolar disorder. In a related study, Zhu et al found that the higher the Child‐Pugh rating, the higher patients scored on two widely used depression and anxiety scales (Hamilton Depression Scale and Hamilton Anxiety Scale). In another China‐based study, controlled for socioeconomic factors, awareness of having hepatitis B increased odds of major depression (OR 1.84 [95% CI: 1.16‐2.90]) compared with patients without hepatitis B .…”
Section: Nonliver Comorbidities Of Chbmentioning
confidence: 98%
“…Interestingly, patients receiving treatment for CHB did not convey an increased risk for bipolar disorder. In a related study, Zhu et al found that the higher the Child‐Pugh rating, the higher patients scored on two widely used depression and anxiety scales (Hamilton Depression Scale and Hamilton Anxiety Scale). In another China‐based study, controlled for socioeconomic factors, awareness of having hepatitis B increased odds of major depression (OR 1.84 [95% CI: 1.16‐2.90]) compared with patients without hepatitis B .…”
Section: Nonliver Comorbidities Of Chbmentioning
confidence: 98%
“…Like patients with other chronic diseases (Katon, 2011), patients with CHB often experience different degrees of psychological distress, such as depression and anxiety. It was reported that the prevalence of depressive symptoms in patients with CHB varied from 16–40.6% (Chan et al., 2012; Keskin et al., 2013; Zhu et al., 2016) and that of anxiety symptoms from 6.7–48.7% (Chan et al., 2012; Vu et al., 2019; Yilmaz et al., 2016) based on different measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to faster improve depression, using the techniques of other therapeutic approaches including the third wave of cognitive behavior therapies combined with cognitive behavior group therapy may be needed. Furthermore, in patients with hepatitis B-associated liver cirrhosis, depression is closely associated with the severity of the cirrhosis [72]. To investigate these instances, extensive research in the future is required.…”
Section: Discussionmentioning
confidence: 99%